Nutritional Status Based on Body Mass Index and Waist Circumference in the Elderly in the Regional Leadership of 'Aisyiyah, Tasikmalaya City - Ida Rosidawati; Nia Restiana; Neni Nuraeni; Lilis Lismayanti; Rosy Rosnawanty; Usman Sasyari; Miftahul Falah (HealthCare Nursing Journal, 2025)
Elderly people are a population group that experiences various physiological changes with age that affect nutritional status. Food consumption and the body's utilization of nutrients can be used to estimate nutritional status. The Body Mass Index and Waist Circumference are two methods used to evaluate the nutritional condition of the elderly. This study purpose to determine the nutritional status based on Body Mass Index and Waist Circumference in the elderly in the Aisyiyah regional leadership of Tasikmalaya City. This research method used a descriptive study with a cross-sectional design. The number of samples in this study was 33 elderly people with an accidental sampling technique. Interviews were conducted with the research subjects to obtain age data, then body weight, height and waist circumference were taken. The analysis used univariate analysis, namely frequency distribution. The results of the study showed that the nutritional status of respondents based on BMI was mostly normal, as many as 19 people (58%), while the nutritional status of respondents based on waist circumference was mostly central obesity, as many as 26 people (79%). Although the nutritional status of respondents based on BMI was mostly normal, most of the respondents' waist circumference experienced central obesity. This deserves attention, because central obesity can increase the risk factors for metabolic and cardiovascular disorders, therefore it is recommended that waist circumference can be reduced.